Interfaith dialogue on environmental ethics at IIUM - Abdul Razak, Mohd Abbas; Muhamad Shukri, Abdul Salam @ Zulkifli (Department of Communication, KIRKHS, IIUM, 2024)
Today, the 3rd of September, was a wonderful experience for most participants who joined the interfaith dialogue on environmental ethics. Many of us at IIUM were fortunate to learn about environmental issues from different religious perspectives. As members of the teaching staff at an Islamic university, we often address the subject of man and nature primarily from an Islamic viewpoint. Listening to people of other faiths discuss what their religious texts say about the proper attitude humans should have towards the environment was thrilling. The two-hour session enriched us in many ways. The Panelists The panelists, each representing different faith groups, were well-versed in their respective religious texts. Dr. Amilah Awang from IIUM discussed environmental ethics from an Islamic perspective. Dr. Living Lee Chai Peng, pastor of the People’s Park Baptist Church, explained the ideal relationship between humanity and nature from a Christian viewpoint. Mr. Parthiban Ramachandran of Hindu Sevai Sangam presented the concept of dharma in man’s relationship to nature. The final panelist, Br. Wong Tin Song provided an overview of the Buddhist perspective on how man should treat nature.